Pengaruh Persepsi Edukasi Kesehatan Terhadap Motivasi Perubahan Perilaku Pasien Rumah Sakit Tipe B Surabaya - Radjak, Nur Afni Rafidah; Mamesah, Marline Merke; Putri, Linta Meyla (Bagian Penelitian & Pengabdian Masyarakat STIKES Adi Husada, 2025)
Background: As an effort by the hospital to carry out promotive, preventive, rehabilitative and palliative efforts to empower patients, Hospital Health Promotion (PKRS) is needed. To achieve this success, media is needed for communication. One of the communication media is Instagram social media. Adi Husada Undaan Wetan Hospital has an Instagram with 20 thousand followers in July 2024 and 1,253 content uploads containing health information and education. Aims: This study aims to determine the effect of Hospital Health Promotion (PKRS) on Motivation for Changing Customer Behavior at the Dental Polyclinic of Adi Husada Hospital, Undaan Wetan, Surabaya. Methods: This study uses data collection techniques through questionnaires with a cross-sectional design, a sample of 73 people. Results: The majority of respondents were aged 18-25 years (36%) and 31-45 years (41%), with the majority of education being college (60%), the majority of occupations being private employees (56%), the majority of incomes > Rp4,525,479 (30%) and the social media used to view health education information Instagram (93%). There is a significant influence between perception and motivation with a sig value of 0.00 <0.05 and has a positive influence (55.9%). Conclusion: In this study, there was a significant influence between respondents' perceptions when viewing social media on the motivation to change customer behavior at Adi Husada Undaan Wetan Hospital, Surabaya.